Murano : Farbe Licht Feuer. (Dresden : Michel Sandstein, 2020)
Murano is considered Italian glass design par excellence. Its tradition goes back to the 14th century. After an eventful history, glass production there experienced a 20th century renaissance that continues today. Works of the highest artistic standards have emerged from the numerous workshops of the island in the lagoon. The catalogue and exhibition present around 300 premium works from one of the world?s largest private collections of Murano glass: the Lutz Holz Collection. The works selected for the exhibition in the GRASSI museum show the many facets of Murano glass as seen in the works of two of the most important glass designers: Ercole Barovier, head of the famous Barovier?&?Toso factory, left a mark on the art glass of the 20th century with his new, experimental techniques. The works of the glass designer Yoichi Ohira typify Murano?s art glass in the 21st century. And in the TECHNE SPHERE exhibition rooms, works in glass from two famous Italian architects are being presented: Carlo Scarpa and Tomaso Buzzi.00Exhibition: Grassi Museum of Applied Arts, Leipzig, Germany (07.11.2020 - 15.08.2021).
boek